2010
DOI: 10.2147/opth.s11007
|View full text |Cite
|
Sign up to set email alerts
|

Predictability and stability of refraction with increasing optical zone diameter in hyperopic LASIK

Abstract: Objective:We undertook a prospective nonrandomized study to assess refractive outcome and patient satisfaction with hyperopic laser in situ keratomileusis (LASIK) using variable optical zone diameters in correction of hyperopia of more than 4.00 diopters.Methods:Fourteen adults (comprising 28 hyperopic eyes) underwent hyperopic LASIK correction for hyperopia of more than 4.00 diopters. The sample was divided into two groups. Group 1 included the right eyes of the 14 patients who underwent hyperopic LASIK using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The percentage of 1-line BSCVA loss was the lowest in the 6 × 9 mm group showing a better safety profile. Lastly, El-Helw and Emarah [ 27 ] concluded that increasing the optical zone diameter is more predictable and stable in the correction of hyperopia. In our study, accuracy and safety were similar to previous studies wherein larger optical zones were used.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of 1-line BSCVA loss was the lowest in the 6 × 9 mm group showing a better safety profile. Lastly, El-Helw and Emarah [ 27 ] concluded that increasing the optical zone diameter is more predictable and stable in the correction of hyperopia. In our study, accuracy and safety were similar to previous studies wherein larger optical zones were used.…”
Section: Discussionmentioning
confidence: 99%
“…Complications in this study were loss of 2 lines in twoeyes (0.74%), loss of 1 line in one eye (0.37%), diffuse lamellar keratitis (DLK) in three eyes (1.13%), prolonged dry eye in nine patients (18 eyes) (6.7%) even after 3 months postoperatively. Loss of lines varies between studies (18, 19), older studies state that the higher hyperopia and the smaller optical zone, loss of lines and less efficient results are expected (7). Later, surgical safety was defined as loss of 2 or more lines of CDVA at 6 months between 1 and 5% (21).…”
Section: Discussionmentioning
confidence: 99%
“…For patients who want to correct hyperopia through refractive surgery, transepithelial photorefractive keratectomy (T-PRK), femtosecond laser-assisted in-situ keratomileusis (FS-LASIK) and small incision lenticule extraction (SMILE) can be used for the correction of hyperopia. These surgical methods can effectively correct hyperopia and ametropia; however, they all increase the risk of corneal swelling, refractive regression, and corneal epithelial implantation after surgery (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%